"I Look at You and See You Looking at Me": Role Boundaries in a Dynamic Research Relationship in Qualitative Health Research With Refugees. (June 2020) - de Smet, Sofie; Rousseau, Cécile; Stalpaert, Christel; De Haene, Lucia
In institutional ethical and deontological guidelines, there is a prevailing, static understanding of the research partnership, with a clear boundary between researcher and participant. In this article, we argue that such a static understanding may run the risk of impeding the development of an enhanced contextual and dynamic intersubjective understanding of the research partnership and its impact on the growing importance of role boundaries in qualitative research. Drawing from a refugee health study on trauma and forced migration, we explore the different ways in which participants and the researcher engaged with the researcher's multiple positions and role boundaries. In doing so, we aim to contribute to a reflective research practice by providing tools to recognize signs of potential harm and offer potential vehicles of reconstruction and agency within the intersubjective space of a dynamic research relationship, within a continuous, shared renegotiation process of role boundaries.